2009
DOI: 10.1016/j.matdes.2008.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and improvement of the quality of Senegalese reinforcing steel bars produced from scrap metals

Abstract: a b s t r a c tSenegalese reinforcing steel bars manufactured from scrap steel exhibit poor welding and bending abilities. The purpose of this study is to evaluate and to correlate the geometrical, mechanical and metallurgical characteristics of these steel bars in order to identify possible causes for their breaking during bending. The relevance of the technical specification defined by the manufacturer and its ability to lead to products of good quality will be discussed. A diagram is proposed to control the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Standardization of size and tensile strengths of steel reinforcement bars should be established for different steel manufacturing industries to enhance reliable design of structures. This should be coordinated by the regulatory agency and the relevant professional bodies [19]. [19] conducted a tensile strengths tests on reinforcing steel bars in the Nige-World Journal of Engineering and Technology rian construction industry and found out that, the characteristic strength for most of the locally produced steel reinforcing bar was low as compared to the 460 N/mm 2 characteristic strength standard values specified in BS 4449, where 60% of the tested samples fell much below the would-be high yield value, rather showing similarities of mild steel bars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standardization of size and tensile strengths of steel reinforcement bars should be established for different steel manufacturing industries to enhance reliable design of structures. This should be coordinated by the regulatory agency and the relevant professional bodies [19]. [19] conducted a tensile strengths tests on reinforcing steel bars in the Nige-World Journal of Engineering and Technology rian construction industry and found out that, the characteristic strength for most of the locally produced steel reinforcing bar was low as compared to the 460 N/mm 2 characteristic strength standard values specified in BS 4449, where 60% of the tested samples fell much below the would-be high yield value, rather showing similarities of mild steel bars.…”
Section: Introductionmentioning
confidence: 99%
“…This should be coordinated by the regulatory agency and the relevant professional bodies [19]. [19] conducted a tensile strengths tests on reinforcing steel bars in the Nige-World Journal of Engineering and Technology rian construction industry and found out that, the characteristic strength for most of the locally produced steel reinforcing bar was low as compared to the 460 N/mm 2 characteristic strength standard values specified in BS 4449, where 60% of the tested samples fell much below the would-be high yield value, rather showing similarities of mild steel bars. These authors also concluded that there is a serious concern that the steel used on sites is falling short of the design expectation because of lack of technical consciousness to test material before being used for control and compliance purposes on sites [4].…”
Section: Introductionmentioning
confidence: 99%